Selection of a Teicoplanin-Resistant Enterococcus faecium Mutant during an Outbreak Caused by Vancomycin-Resistant Enterococci with the VanB Phenotype - Kawalec, Magdalena (American Society for Microbiology, 2001)
Vancomycin-resistant enterococci (VRE) have recently become an increasing problem in hospitals in Poland, being responsible for a growing number of nosocomial outbreaks. In this work, we have analyzed the second outbreak of VRE with the VanB phenotype to be identified in the country. It was caused by clonal dissemination of a single strain of vancomycin-resistant Enterococcus faecalis (VRES) and horizontal transmission of vancomycin resistance genes among several vancomycin-resistant Enterococcus faecium (VREM) strains. Two similar restriction fragment length polymorphism types of the vanB gene cluster characterized VRES and VREM isolates, and they both contained the same vanB2 variant of the vanB gene. Two vancomycin-susceptible E. faecium (VSEM) isolates, recovered from the same wards during the outbreak, proved to be related to certain VREM isolates and could represent endemic strains that had acquired vancomycin resistance. One VSEM and four VREM isolates, all identified in the same patient, belonged to a single clone, although they revealed remarkable diversity in terms of susceptibility, PFGE patterns, plasmid content, and number of vanB gene cluster copies. Most probably they reflected the dynamic evolution of an E. faecium strain in the course of infection of a single patient. One of the VREM isolates turned out to be resistant to teicoplanin, which coincided with the use of this antibiotic in the patient's therapy. Its vanB gene variant differed by a single mutation from that found in other isolates; however, it also lacked a large part of the vanB gene cluster, including the regulatory genes vanR(B) and -S(B), and the vancomycin-inducible promoter P(YB). Expression of the resistance genes vanH(B), -B, and -X(B) was constitutive in the mutant, and this phenomenon was responsible for its unusual phenotype.